Introduction of New Technologies in Orthopaedic Surgery. Issue 5 (24th May 2016) - Goodman, Stuart B.; Mihalko, William M.; Anderson, Paul A.; Sale, Katherine; Bozic, Kevin J.
Abstract : The introduction of new devices, biologics, and combination products to the orthopaedic marketplace is increasing rapidly. The majority of these new technologies obtain clearance to market by demonstrating substantial equivalence to a predicate (previously approved device) according to the U.S. Food and Drug Administration (FDA) 510(k) process. Surgeons play a critical role in the introduction of new technologies to patients and must take a leadership role in promoting safe, efficacious, appropriate, and cost-effective care, especially for operative procedures. Surgeons should monitor and document their patients' clinical outcomes and adverse events when using new technology, to ensure that the new technology is performing as desired.